A Causal-Comparative Study of the Effect of Differing Levels and Years of Experience on Christian Teachers’ Instructional Differentiation Scores - Carver, Lin B.; Locklear, Audra Callahan (Advances in Social Sciences Research Journal, 2025)
This causal comparative study examines the differentiation practices Christian school teachers use in serving their students and whether these are impacted by their level of employment (elementary or secondary) and their length of employment. This study involved 123 U. S. Christian school teachers who were recruited through social media. Based on the results from the Classroom Practices Survey, statistical analysis was completed using a two-way ANOVA to examine the frequency of differentiation methods used by level of employment level and length of employment at Christian schools. Based on the results, the researcher accepted the two-way null hypothesis of no significant difference in the overall teacher differentiation score as measured by the Classroom Practices Survey, between levels of employment (elementary and secondary) and years of experience on the Classroom Practices Survey. However, there was a significant difference based on level of employment (elementary or secondary). Thus, the conclusion is made that the use of differentiated instructional strategies has a greater presence at the elementary level in Christian schools than at the secondary level.